2007
DOI: 10.1097/01.mpg.0000302969.60373.39
|View full text |Cite
|
Sign up to set email alerts
|

Extensive and Partial Protein Hydrolysate Preterm Formulas

Abstract: Protein hydrolysate formulas for preterm infants recently have been developed. However, the indications for the use of such formulas are unclear. The aim of this article is to systematically evaluate the effect of protein hydrolysate formulas in the feeding of preterm infants through searching the MEDLINE (1966-August 2006) and Cochrane Library (Issue 4, 2006) databases. There is little evidence to support the use of extensive and partial protein hydrolysate formulas for preterm infants. High quality, long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However a recent study did not find any advantage of hydrolysed over whole-protein formula33 or breast milk34 and a review of the literature up to august 2006 concluded that there was insufficient evidence to warrant routine use of these feeds for preterm infants 35…”
Section: Types Of Feedmentioning
confidence: 99%
“…However a recent study did not find any advantage of hydrolysed over whole-protein formula33 or breast milk34 and a review of the literature up to august 2006 concluded that there was insufficient evidence to warrant routine use of these feeds for preterm infants 35…”
Section: Types Of Feedmentioning
confidence: 99%
“…After removing duplicates, 374 titles and abstracts were assessed by two reviewers, who identified 55 records for full text assessment. Forty-one articles were subsequently excluded for a variety of reasons including: lack of a systematic search for studies addressing the outcome of food allergy [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55]; no reported individual food allergy outcomes [56,57,58,59,60]; protocol or abstract only [61,62,63,64,65]; withdrawn from the literature [66]; earlier version of updated review [67]; Chinese language [68] and; unable to locate [69]. …”
Section: Resultsmentioning
confidence: 99%
“…In 2007, Szajewska [33] reviewed the effect of HPFs on feeding tolerance in three studies. In the study by Riezzo et al [34] , no difference was observed between infants fed HPF (n = 18) or sPTF (n = 18) although regurgitation and vomiting were very frequent (64 and 78%, respectively).…”
Section: Gastrointestinal Transit Time and Feeding Tolerancementioning
confidence: 99%
“…10 vs. 12 , range 9-27 vs. 9-28 days; p = 0.0024). In her review, Szajewska [33] concluded that despite some potential clinical advantages, like shorter time to achieve full feeding, it is unclear whether the use of HPFs should be adopted as routine practice because of its limited information regarding nutritional adequacy.…”
Section: Gastrointestinal Transit Time and Feeding Tolerancementioning
confidence: 99%